2013
DOI: 10.5415/apallergy.2013.3.2.106
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of pediatric anaphylaxis and the necessity for multiple doses of epinephrine

Abstract: BackgroundEpinephrine administered intramuscularly is the treatment of choice for anaphylaxis, and more than 1 dose is occasionally required.ObjectiveTo determine clinical background of anaphylaxis for improving the treatment, management, and prognosis of anaphylaxis.MethodsChildren who had satisfied the diagnostic criteria for anaphylaxis according to the National Institute of Allergy and Infectious Disease Food Allergy and Anaphylaxis Network were selected from our hospital from April 1, 2009 to March 31, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 23 publications
0
35
1
1
Order By: Relevance
“…38 The association of a biphasic reaction with the severity of the initial reaction has just recently emerged as a potential risk factor. 39 23,34 Although these studies provide some insight about this association, the reported cases are too small to reliably predict this association. Also, the definition of severity used in these studies is inconsistent and not based on objective scoring.…”
Section: Previous Studiesmentioning
confidence: 81%
“…38 The association of a biphasic reaction with the severity of the initial reaction has just recently emerged as a potential risk factor. 39 23,34 Although these studies provide some insight about this association, the reported cases are too small to reliably predict this association. Also, the definition of severity used in these studies is inconsistent and not based on objective scoring.…”
Section: Previous Studiesmentioning
confidence: 81%
“…For the critical outcome of resolution of symptoms, we identified very-low-quality evidence (downgraded for risk of bias and confounding) from 9 observational studies [77][78][79][80][81][82][83][84][85] showing benefit for giving a second dose (or multiple doses) of epinephrine to patients not responding to a first dose (RR, 1.16; 95% CI, 1.13-1.20).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Ausgebildete Ersthelfer können bei dieser Maßnah-me unterstützen. Geben Sie allen Personen mit einer Anaphylaxie im präklini-schen Bereich eine zweite intramuskuläre Adrenalindosis, wenn sich die Symptome innerhalb von 5-15 min nach der Anwendung eines intramuskulären AdrenalinAutoinjektors nicht gebessert haben [843][844][845][846][847][848][849][850][851][852]. Auch bei einem Wiederauftreten der Symptome kann eine zweite intramuskuläre Dosis Adrenalin notwendig sein.…”
Section: Zweitgabe Von Adrenalin Bei Anaphylaxieunclassified